The AD Knowledge Portal: A Repository for Multi‐Omic Data on Alzheimer's Disease and Aging. (21st October 2020) - Greenwood, Anna K.; Montgomery, Kelsey S.; Kauer, Nicole; Woo, Kara H.; Leanza, Zoe J.; Poehlman, William L.; Gockley, Jake; Sieberts, Solveig K.; Bradic, Ljubomir; Logsdon, Benjamin A.; Peters, Mette A.; Omberg, Larsson; et al.
Abstract: The AD Knowledge Portal (adknowledgeportal.org) is a public data repository that shares data and other resources generated by multiple collaborative research programs focused on aging, dementia, and Alzheimer's disease (AD). In this article, we highlight how to use the Portal to discover and download genomic variant and transcriptomic data from the same individuals. First, we show how to use the web interface to browse and search for data of interest using relevant file annotations. We demonstrate how to learn more about the context surrounding the data, including diagnostic criteria and methodological details about sample preparation and data analysis. We present two primary ways to download data—using a web interface, and using a programmatic method that provides access using the command line. Finally, we show how to merge separate sources of metadata into a comprehensive file that contains factors and covariates necessary in downstream analyses. © 2020 The Authors. Basic Protocol 1 : Find and download files associated with a selected study Basic Protocol 2 : Download files in bulk using the command line client Basic Protocol 3 : Working with file annotations and metadata